Politeness Strategy of Directive Utterance By The Host of Satu Jam Lebih Dekat Talk Show - Sumarni, Sumarni (Abdurrauf Journal of Islamic Studies, 2023)
This study deals with the politeness strategies of directive utterance by the host of satu jam lebih dekat talk show. This study employs qualitative design which aims at describing the politeness strategy of directive utterance by the host. The results show that the host expresses her directive utterances in request, questions, interrogate, urge, invite, and caution. The host applied the four types of politeness strategies to relate directive utterances as politeness strategies stated by Brown and Levinson they are (1) bald on record, (2) positive politeness, (3) negative politeness, (4) off record. The most types is question (12.56%) as positive politeness. It is caused by the host wants to give questions respects the H’s negative face want and will not (or will only minimally)interfere with the H’s freedom of action